1998
DOI: 10.1046/j.1469-8137.1998.00219.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soil compaction on phosphorus uptake and growth of Trifolium subterraneum colonized by four species of vesicular–arbuscular mycorrhizal fungi

Abstract: The ability of four species of vesicular-arbuscular mycorrhizal (VAM) fungi to increase phosphorus uptake and growth of clover plants (Trifolium subterraneum L.) at different levels of soil compaction and P application was studied in a pot experiment. Dry matter in the shoots and roots of clover plants decreased with increasing soil compaction. Colonization by Glomus intraradices Schenck & Smith and Glomus sp. City Beach WUM 16 increased plant growth and P uptake up to a bulk density of 1n60 Mg m −$ , a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 38 publications
0
33
0
2
Order By: Relevance
“…The reduction of the largest pores have in several other studies been shown to be one of the most important consequences of soil compaction (Oussible et al 1992;Nadian et al 1996;Nadian et al 1997;Nadian et al 1998;Richard et al 2001). Root growth is likely to be hampered by excessive compaction, and there may be problems with the transport of oxygen, water and nutrients in the soil.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The reduction of the largest pores have in several other studies been shown to be one of the most important consequences of soil compaction (Oussible et al 1992;Nadian et al 1996;Nadian et al 1997;Nadian et al 1998;Richard et al 2001). Root growth is likely to be hampered by excessive compaction, and there may be problems with the transport of oxygen, water and nutrients in the soil.…”
Section: Resultsmentioning
confidence: 96%
“…This requires energy, and is an important reason for reduced root elongation. Root stunting and thickening have in several studies shown to be the most prominent morphological changes of roots growing through mechanically impeding media (Oussible et al 1992;Lipiec et al 1996;Nadian et al 1996;Nadian et al 1998;Chassot et al 2001). The radial thickening is associated primarily with shorter and wider cells with the same volume in the cortex and with thicker cortex (Fitter 1996).…”
Section: Root Growthmentioning
confidence: 95%
“…This is in accordance with studies demonstrating that the presence of plant have the greatest impact on structure generation, with AMF also contributing to accentuate soil stability (Hallett et al, 2009;Jastrow et al, 1998). The possibility of differential AMF response to soil compaction was described by Nadian et al (1998). As the diameter of external hyphae is smaller than roots it may penetrate smaller pores and enhance the observed leek roots effect and stimulate plant exudates secretion, thus increasing bacterial activity.…”
Section: Discussionmentioning
confidence: 99%
“…AM plants can therefore potentially access nutrients from drier or more compacted soils (i.e. smaller pores) than can NM equivalents (Nadian et al 1998;Tobar et al 1994). Operation of the AM nutrient uptake pathway will therefore persist at lower (more negative) soil water potentials than direct uptake via root epidermis (Drew 2002) and root hairs.…”
Section: Exploration Of Soil By External Mycelium and Interactions Wimentioning
confidence: 98%